Integrating Axiology In Language Education: Philosophical Foundations And Humanistic Implications - Sri Wulandari; Muhammad Ridho Anshori (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2025)
This study seeks to examine the integration of the axiology of the philosophy of science into language teaching and to explore its transformative implications for language proficiency development grounded in humanistic values. Adopting a qualitative library research methodology, the study systematically analyses a carefully selected corpus of scholarly sources — including peer-reviewed journals, academic monographs, and authoritative articles — based on their relevance to the intersections of philosophy of science, language pedagogy, and humanistic education. The findings indicate that embedding axiological principles within language teaching substantially enriches the educational process. It not only enhances fundamental linguistic competencies such as grammar, vocabulary, and discourse skills but also cultivates ethical dimensions, including empathy, justice, and intercultural understanding. This integrated approach enables learners to become ethically conscious and socially responsible communicators, capable of navigating complex cross-cultural interactions in an increasingly globalised environment. Furthermore, the study demonstrates that axiological integration fosters reflective and value-oriented pedagogical practices, aligning language education with broader educational objectives such as character formation, ethical literacy, and the promotion of social cohesion. In conclusion, the research introduces a novel pedagogical paradigm by positioning axiology as a foundational element in language teaching. This value-based approach redefines the objectives of language education, contributing significantly to the creation of inclusive, equitable, and culturally sensitive societies equipped to address communication challenges in a multicultural world.